Diabetes in the Pediatric Age Group: A Case Series and Review of Literature - Jesús Rodolfo Valenzuela-Ruiz; Gustavo Francisco Bobadilla-Olaje; Jesús René Tadeo Calleja-López; Enrique Ruibal-Tavares; Cristian Noé Rivera-Rosas; Luis José Aguilera-Duarte; Jesús Omar Ruiz-Quiroz (Mazandaran University of Medical Sciences, 2023)
Background: Diabetes mellitus (DM) is characterized by sustained hyperglycemia (HG), which has multiple etiologies. The American Diabetes Association (ADA) classifies DM into four major groups. In the pediatric age, DM can be caused by several etiologies. Case Presentation: We present a series of four case reports of DM among pediatric patients caused by different etiologies, to discuss several clinical presentations of DM among children and the teenage population, as well as diverse therapeutic options for the different DM subtypes. Conclusions: We conclude that DM in the pediatric age group has multiple etiologies and presentation variants. Type 1 DM still represents the highest incidence in this age group, however, several factors have aided in the awareness and diagnosis of other types of DM previously considered as rather infrequent in this age group.